Difficulties of Teaching Speaking Competence in EFL Classes and Effective Methods to Overcome Them - Qizi, Ismatullayeva Mamura Farxritdin (Journal of Innovation in Education and Social Research, 2025)
The address of the head of our state emphasized the need to achieve a level that would allow students of any secondary school to learn English at a high level. In general, special attention is paid to the study of a foreign language in educational institutions. In addition, for this it is necessary to get acquainted with the practice of foreign scientists on the methodology of language teaching. The article discusses the main difficulties that secondary school students encounter in the process of learning to speak in English lessons, possible ways to solve them, including problem situations as the most effective method that corresponds to the age-related psychological and pedagogical characteristics of secondary school students. level students.